Penerapan Teknologi Modern Dalam Petualangan Di Novel Komet Karya Tere Liye - Yulanda; Elio Phillo Rismanto, Muhammad (Shofanah Media Berkah, 2023)
This research aims to analyze the application of modern technology in the adventures of the main characters in the novel Komet by Tere Liye. By using a hermeneutic approach, researchers understand and interpret how modern technology is depicted and utilized in the fictional adventures of the characters on an alien planet. The researcher used qualitative research methods as the main instrument to identify factors and information contained in the novel. The research results show that modern technology is widely applied in the adventures of the main characters, such as 1) remote control, 2) technology, 3) online transportation, 4) electronic devices, 5) three-dimensional digital projection, and 6) internet streaming. The application of this technology provides new insight into literary studies regarding the development of modern technology and its use in the contemporary fiction genre. In this novel, modern technology is not only a tool but also an important element that influences the flow of the story and character interactions. Thus, the application of modern technology also enriches the dimensions of adventure and fiction in literary works.